Living and Dying for Work: An analysis of the Banality of Evil in Corporate Crimes - Silveira, Rafael Alcadipani da; Medeiros, Cintia Rodrigues Oliveira (Organizações & Sociedade, 2014)
In this paper, we explore the concept and origins of corporate crime to discuss such crimes related to the death of workers. Our objective is to open a dialogue with organizational sociologist dealing with the dark side of organizations as well as the concept and origins of corporate crime. We refer the thought of Hannah Arendt on the banality of evil to order the proposed dialogue: do the actions that are intended to achieve the business goals and involve the death of workers banalize the notion of corporate crime? For this paper we use the journalistic documentary research files on deaths at work, including both those caused by accidents at work, as well, suicides, as a mean of illustration. As a result, we present two reports of deaths at work that trigger the need for reflection on the banality of evil in corporate crime.